INNOVATIONS AND COERCION: THE EVOLUTION OF OPIUM POPPY PRODUCTION IN COLONIAL INDIA - Vigya Tripathi, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The British opium monopoly in colonial India underwent significant transformation through a series of strategic interventions aimed at enhancing production efficiency. Efforts spanned from seed selection to factory processing, with substantial investments in irrigation and cost-cutting measures. Despite the pervasive role of coercion, technological and managerial innovations were crucial. The monopoly faced challenges from other suppliers, the need for product uniformity in an export market, and the natural variability of opium. Continuous adaptation and innovation were necessary to sustain profitability. This paper studies measures such as hydraulic machinery, improved packaging, and financial incentives for innovation, highlighting the complex interplay between economic imperatives and operational challenges. The findings contribute to a deeper understanding of the British opium monopoly's economic and operational dynamics.